Corrosion behavior of GO‐reinforced TC4 nanocomposites manufactured by selective laser melting. Issue 4 (13th November 2019) - Liu, Xin; Wu, Meiping; Lu, Peipei; Ye, Xiu; Miao, Xiaojin
Abstract: To improve the corrosion resistance of Ti–6Al–4V (TC4) matrix, the influence on the corrosion behavior, microhardness, and microstructure of graphene oxide (GO)‐reinforced TC4 nanocomposites manufactured by selective laser melting was systematically investigated in this study. Microhardness tester, profilometer, X‐ray diffractometer, scanning electron microscopy, and electrochemical workstation were used to characterize the association between microhardness, pore microstructures, hard phases, and corrosion resistance of GO/TC4 nanocomposites. It can be observed that the incorporation of GO promotes the in situ formation of hard phases, such as TiC, TiO2, Al2 O3, and so forth, and it also changes the microstructure of the matrix as well as increases its porosity. Nevertheless, GO/TC4 nanocomposites perform the best corrosion resistance when the mixing content of GO is 0.5 wt%, and its microhardness is greatly improved with the addition of GO. All experimental results suggest the efficacy of added GO. Abstract : The evolution law of composition, structure, and properties of graphene oxide reinforcement in Ti–6Al–4V (TC4) matrix has been systematically investigated in this study. The corrosion resistance of TC4 nanocomposites manufactured by selective laser melting has been improved compared with pure TC4, and the relation between hard phases, porosity, and corrosion resistance has been revealed.